Demographic changes in the area of Śląskie voivodeship - retrospective analysis and projection until 2050 - Sojka, Elżbieta (Bulletin of Geography. Socio-economic Series, 2016)
The purpose of the paper is to present already observed as well as expected changes in the condition and age structure of the population of Śląskie voivodeship. The analysis concerns the years between 1990 and 2050. The paper presents changes in population in the years from 1990 to 2013 and the projection of the population situation in 2050. Special attention is focussed on the process of changes in population functional age groups, also the dynamics and the level of ageing advancement of population in total as well as of particular age groups which are significant from the point of view of labour market and future births are presented.